Analysis of Key Factors Affecting the Coke Pushing Stability of Coke Pusher - Jin Xiang (Shock and Vibration)
In order to find out the key factor affecting the stability of coke pusher, the structural deformation and vibration mode parameters of the coke pusher are obtained by thermal-structural coupling simulation and thermal-modal coupling simulation, and the vibration signals in the process of coke pushing are collected for time-domain analysis and time-frequency analysis. The results show that the coke pusher vibrates after being affected by the friction, and the vibration frequencies are close to the natural frequencies; that is, the friction has a great influence on the stability of the coke pushing rod. In addition, affected by the friction, the deformation of the bottom of coke pusher is the largest, resulting in unstable contact between the bottom of coke pusher and the ground of carbonization chamber, which is very easy to cause vibration.